The Performance of MSMEs: a Comprehensive Approaches based on Resource, Customers, Suppliers, and Characteristics of MSMEs - Sri Wahjuni Latifah; Ahmad Waluya Jati; Mudrifah - (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2021)
This study focuses on MSMEs performance evaluation because they have unique features such as not having a quantifiable objective, not having a record of company operations, but being able to absorb surrounding labor and improve the community's welfare. MSMEs' short-term objective is to annex the company's profit and sales performance. This research aims to construct a measurement model of MSMEs Performance based on resource factors, customers, suppliers, and characteristics of MSMEs in influencing MSMEs' performance. The data was collected by spreading questioner through google form to MSMEs managers assisted by PLUT Batu city and Malang City. The data analysis techniques are carried out qualitatively, and hypothesis testing is carried out with SEM-PLS analysis. The results showed that the factors of resources, customers, and characteristics of MSMEs could measure MSMEs performance, while the supplier factor does not affect the performance of MSMEs